Предмет: Алгебра,
автор: blastka
Нужно упростить выражение:
Приложения:
Ответы
Автор ответа:
0
а) к общему знаменателю:
(sint*(1-cost)+sint(1+cost))/(1-cos^2t)=(2sint)/(sin^2t)=2/sint
в) к общему знаменателю:
(cost(1-sint)+cost(1+sint))/(1-sin^2t)=2cost/cos^2t=2/cost
Как-то так
(sint*(1-cost)+sint(1+cost))/(1-cos^2t)=(2sint)/(sin^2t)=2/sint
в) к общему знаменателю:
(cost(1-sint)+cost(1+sint))/(1-sin^2t)=2cost/cos^2t=2/cost
Как-то так
Похожие вопросы
Предмет: Математика,
автор: ilvina500
Предмет: Биология,
автор: gabibbabaev08167
Предмет: География,
автор: Narkorn74
Предмет: Математика,
автор: Shugik
Предмет: Математика,
автор: Эрудит567